Board independence and internal control quality in Egypt: does CEO duality matter?. Issue 2 (4th April 2019) - Khlif, Hichem; Samaha, Khaled
Abstract : Purpose: This paper aims to examine the relationship between board independence and internal control quality (ICQ) in Egypt and investigate whether CEO duality moderates such an association. Design/methodology/approach: A survey among external auditors is used to assess ICQ among Egyptian listed firms over the period of 2007-2010. Findings: Findings show that board independence does not have a significant positive effect on ICQ. However, when testing for the moderating effect of CEO duality on such a relationship, the authors document that the association becomes positive and significant under combined board leadership structure, whereas it is negative under separated leadership structure. Originality/value: The authors' results demonstrate that CEO duality plays a governance role in weak legal environment like Egypt by strengthening board independence role in increasing ICQ.